If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(2 + -8n) = 186 (2 * -3 + -8n * -3) = 186 (-6 + 24n) = 186 Solving -6 + 24n = 186 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 24n = 186 + 6 Combine like terms: -6 + 6 = 0 0 + 24n = 186 + 6 24n = 186 + 6 Combine like terms: 186 + 6 = 192 24n = 192 Divide each side by '24'. n = 8 Simplifying n = 8
| 4x+3(5-13)=132 | | 2x+3y-8z=89 | | 6x+2(x+7)=-10 | | 3s+8=-10 | | -5(2-5k)-6=134 | | 408.33=95-2x | | 3t+4=500+t | | 4(x-5)=12+x+x | | -4(x-6)-7=39 | | 16=4w+2w?2 | | -6(1+7n)=-132 | | 9/11=a | | 2x+7y=1000 | | 5(x-6)+9=43 | | -2f/3=2 | | 5(6-8x)=-130 | | -3(x-7)=17 | | 2y-5=y-2 | | 2/7=r | | 14x+70=7 | | 2(x+11)=54 | | (x^3)+(5x^2)-9x-45=0 | | 3b=-9 | | 3000-120x=15000 | | 93-(4m-8)=53 | | 2(3c)=36 | | f=(12)60-2/3r | | X*2+x*2=-14-3 | | -200x-2500=5100 | | -124=-4v-2(6+6v) | | -4x-18=73 | | y=x/2-13^3 |